Financial contagion in the US, European and Chinese stock markets during global shocks - Marina Yu. Malkina (Journal of New Economy)
Under globalisation, integration, and financialisation of national economies, the financial markets’ interdependence tends to swell, which increases the probability of financial disturbances spreading between countries, especially during global shocks, and calls for the development of new standards of financial regulation. The article studies the financial contagion among stock markets of different countries during global shocks associated with the COVID-19 pandemic, the energy crisis, and the special military operation of Russia in Ukraine (SMO). The concept of financial contagion underlies the methodology of the research. The financial contagion is diag nosed based on the construction of DCC-GARCH models and the calculation of dy namic conditional beta coefficients. Causal relationships in the interaction of indices are established using the Granger test. The data are average daily indices: the Ameri can S&P 500, the European STOXX 600, and the Shanghai Stock Exchange (SSE) Composite Index – for December 2018 – March 2024 obtained from the financial portal Investing.com. The study reveals a high level of connectivity in normal times between the American and European stock markets with some autonomy of the Chinese stock market. However, during the 2020 pandemic, there was a short-term strong contagion of the S&P 500 and STOXX 600 from the SSE Composite Index, as well as longer-term, moderate cross-contagion between the S&P 500 and STOXX 600. During the 2021 energy crisis and SMO, there was strong and relatively long-lasting contagion of the S&P 500 from the STOXX 600 and their much weaker contagion from the SSE Composite Index. The findings may be useful for stock market players in managing investment portfolios, and for the state in formulating financial stabilisation policies during the impact of global shocks.